Perpetuation of Stigmatization of Minority Groups through Convergence of Content on Streaming and Social Media - Setiawan, Yuliyanto Budi; Sarwono, Billy K.; Asteria, Donna; Sunarto, Sunarto (Jurnal The Messenger, 2022)
Introduction: This study aims to show the misrepresentation of minority groups, specifically widowed women (hereinafter referred to as janda) in the era of convergence of media content (television as well as streaming and social media) in Indonesia. Media as the fourth pillar of democracy are supposed to inform and represent everything in a balanced and fair manner, instead of favoring the interests of the majority. The question we attempt to answer is: how the misrepresentation of janda on converged media content (FTVs) in a patriarchal society?Methods: This study applied feminist perspective in media convergence as well as the narrative analysis of Chatman.Findings: In general, the results of the study show that the convergence has not been in favor of janda, indicating that internet technology does not only strengthen the gender-biased values of media industry person in massively distributing FTVs (via streaming and social media) that threaten minorities, but also ignores the opposing feedback from netizens. As a result, the minority groups are increasingly muted. Reproduction of labelling of janda is a strategy of media owners to obtain maximum profits.Originality: We noted many studies on janda conducted from various scientific perspectives. However, studies that observe the depiction of janda in the media convergence in the perspective of communication studies are scarce. This study provides a discussion on the representation of janda in the vortex of capitalism in media convergence as the major novelty in this line of study.